Childhood Statelessness: Critiquing International Norms and Enforcement Strategies - R K, Biju (Brawijaya Law Journal : Journal of Legal Studies, 2021)
Over the past decade, there has been renewed interest in and commitment to resolving the endemic problem of statelessness, most clearly exemplified by the United Nations High Commissioner for Refugees’ Global Action Plan to End Statelessness 2014-24, which sets out to end statelessness by 2024. Despite the plethora of recent attention to questions of citizenship, its converse, the problem of statelessness and its effect on children, has not been adequately investigated. This paper attempts to delineate the causes of childhood statelessness in particular and to analyze the international legal framework for reducing and preventing it. It examines how statelessness is created, how it persists and why it brings with it the deprivations it does. It then subjects the customary and modern international legal norms governing childhood statelessness and enforcement strategies at Global level to close scrutiny and identifies the clearly discernible drawbacks and road blocks. It concludes with suggestions, inter alia, to make the jus soli citizenship a mandatory default clause in the citizenship laws of every country, to further prioritize birth registration and data collection and to strengthen the UPR process and reporting procedure.